Pomalidomide experience: an effective therapeutic approach with immunomodulatory drugs in a patient with relapsed-refractory multiple myeloma. (February 2017) - Conticello, Concetta; Parisi, Marina; Romano, Alessandra; Calafiore, Valeria; Ancora, Flavia; La Fauci, Alessia; Consoli, Maria Letizia; Di Raimondo, Francesco
Here we discuss the case of a heavily pretreated male patient with relapsed-refractory multiple myeloma and previous monoclonal gammopathy of undetermined significance who initiated a fifth-line treatment with pomalidomide (4 mg orally, days 1–21 of a 28-day cycle) and low-dose dexamethasone (40 mg weekly orally). A total of 3 months later, very good partial response was achieved and complete response was maintained for 7 months. This case illustrates the field-practice experience on the benefits of pomalidomide in a relapsed-refractory multiple myeloma patient with a previous history of monoclonal gammopathy of undetermined significance. Indeed, the pomalidomide/dexamethasone regimen resulted in a longer progression-free survival compared with previous regimens and demonstrated a good long-term tolerability.